Peran dan Strategi serta Kendala BPBD dalam Menanggulangi Banjir Rob di Kota Tembilahan - Supraptono (Indra Institute Research & Publication, 2024)
In writing this article the author used library research methods and also collected data using qualitative methods by interviewing or interviewing several sources where Tembilahan is an area in Riau province which has many ditches and types of peat soil and every year Tembilahan is always prone to flooding. tidal floods and on January 25 2023 Tembilahan was hit by the worst tidal floods in recent years. The tidal flood itself is a tidal flood caused by sea water that overflows and inundates the land. Based on this, the formulation of the problem in this paper includes (1) What is the role of the BPBD of Tembilahan city in overcoming tidal floods that continuously occur in Tembilahan (2) What are the strategies of the BPBD of Tembilahan city in overcoming tidal floods and (3) What are the obstacles? faced by BPBD Tembilahan in dealing with the tidal flood disaster. So the conclusions of this research are (1) the role of regional disaster management agencies in the disaster management process is very important where in the stages of the disaster management implementation process it can start with disaster prevention itself, emergency response and rehabilitation and reconstruction, another role of BPBD is to carry out several planning in an effort to reduce the risk of tidal floods, apart from carrying out emergency response and playing an active role in providing education to the community, (2) the strategy carried out by BPBD Tembilahan to overcome tidal floods is to make efforts to revitalize the ditches in Tembilahan, carry out mitigation and planting mangroves on seashores and coastlines, (3) however, in the process of implementing disaster management, there are certainly several obstacles, including cost constraints, insufficient human resources, inadequate infrastructure and lack of public awareness about disasters, resulting in The process of implementing flood disaster management is difficult to implement.